Level of Vocabulary Development and Selected Elements Regarding Sensory Integration and Balance in 5-Year-Old Girls and Boys - Jacek Wilczyński; Grzegorz Ślęzak (MDPI AG, 2021)
The aim of this research was to assess relationships between the level of vocabulary and selected elements of sensory integration and balance in 5-year-old girls and boys, showing the differences between them. The study group consisted of 290 5-year-old children (172 boys and 118 girls) with different levels of vocabulary development and selected disturbances in sensory integration and balance processes. To evaluate the developmental deficits of speech with regard to vocabulary, the Children's Dictionary Test was used. The Clinical Test of Sensory Integration and Balance was also employed. In our research's overall assessment, 118 children, i.e., 41%, had a low level of vocabulary, while 108 (37%) had an average level and 64 (22%) had a high level. However, the average score of all examined children (3.71 stens) indicates a low level of vocabulary development. Less developed vocabulary skills included the ability to create subordinate words and define concepts. There were no significant differences in the level of vocabulary between girls and boys. We observed disorders concerning selected elements of sensory integration and balance in most of the children, and more often in boys. There were statistically significant relationships between the level of vocabulary and selected disorders of sensory integration and balance; however, they were not unambiguous. Children with the lowest level of vocabulary in overall assessment obtained significantly the worst results in the Clinical Test of Sensory Integration and Balance (CTSIB) open eyes, hard surface test. However, in the closed eyes, hard surface test, the lowest score was obtained by children with a high overall assessment. In turn, in the open eyes, soft surface test, the lowest score was noted for children with average overall assessment. In the complex CTSIB test, the lowest score was achieved by children with low ability to define concepts. The problem of the relationship between vocabulary level of and sensory integration as well as balance requires further research. The demonstrated significant relationships between some aspects of vocabulary level and selected elements of sensory integration as well as balance confirm the need to care for the overall psychomotor sphere of a child.